A study on the factors that influence non adoption of i-Rakyat among Bank Rakyat consumers in Nilai branch / Rosnah Husin - Husin, Rosnah (2010)
This thesis is especially prepared to study the factor influencing non adoption of internet banking, called i-Rakyat. To complete and make this thesis become stronger and also being more helpful, I have collected and analyze much of previous studies and research done by qualified researchers and also few references from various journal and business websites. A questionnaire was used to acquire data from 70 customers who are not i-Rakyat users. Non probability sampling is using where the elements in the population do not have any probabilities attached to their being chosen as sample subjects. The data obtained will be analyzing using Statistical Package for the Social Science (SPSS). This thesis is contained of eight chapters and five factors were identified as independent variables. There are perceived risk, lack of perceived need, lack of knowledge about the service, inaccessibility and lack of human touch. The factors appear to provide a comprehensive understanding of why certain consumers are not i-Rakyat users. The factors provide a useful basis for researchers to conduct studies for better understand what influences consumers decision not to use the internet as a means of sourcing banking services. The findings create an awareness of a various reasons explaining why consumers are not adopting i-Rakyat. The various reasons provide scholars with an opportunity to conduct further research in this area and practitioners with an opportunity to enhance adoption rates.